189 Genetic Variation in ADAMTS7 is Associated with Severity of Coronary Artery Disease. (6th June 2015) - Chan, Kenneth; Patel, Riyaz; Pu, Xiangyuan; Ng, Fu-Liang; Simpson, Iain A; Poston, Robin N; Ye, Shu; Quyyumi, Arshed; Hayek, Salim
Abstract : Purpose: Genome-wide association studies have identified ADAMTS7 as a risk locus for coronary artery disease (CAD) and myocardial infarction (MI). Functional studies suggest ADAMTS7 may promote cellular processes in atherosclerosis. We studied if risk variant carriers exhibit a greater burden of angiographic CAD. Methods: We genotyped ADAMTS7 in the Southampton Atherosclerosis Study (SAS, n = 1359), and replicated in the Emory Genebank (Emory GB, n = 2684). Angiographic CAD was phenotyped as presence of >50% stenosis in epicardial vessel and semi-quantitative scores including the Gensini Score (GS), Sullivan Extent Score (SES) and the Duke Severity Index (DSI); and ex-vivo immunohistochemical analysis of human coronary plaques (n = 48). Results: We confirmed an association between ADAMTS7 genotype and presence of CAD under an additive genotype model in SAS (p = 0.05) and Emory GB (p = 0.017), but found no associations with MI in the presence of CAD. ADAMTS genotypes were associated with all of the angiographic severity scores in SAS (GS p = 0.017, SES p = 0.045, DSI p = 0.029), and independently replicated in Emory GB (GS p < 0.001, SES p < 0.001, DSI p = 0.001). Meta-analysis demonstrated that homozygous carriers of the risk allele had greater odds of multi-vessel disease [OR 1.36 (95% CI 1.13–1.63)] and proximal stenoses [OR 1.41 (95% CI 1.15–1.72)], compared to non-risk allele carriers. Additionally, the risk genotype was associated with greater fibrous cap thickness (p = 0.013) and% area of α-actin (smooth muscle cell marker) in the intima (p = 0.029). Conclusions: The ADAMTS7 risk variant is associated with multiple angiographic measures of CAD burden and plaque remodelling, further supporting the role of this protease in promoting atherosclerosis.